2004
DOI: 10.1177/153303460400300301
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Planning of Cryosurgery Using Cryoprobes and Cryoheaters

Abstract: In a typical minimally invasive cryoprocedure, multiple cryoprobes are inserted into the tissue with the goal of maximizing cryoinjury within a predefined target region, while minimizing cryoinjury to the surrounding tissues. A temperature-controlled electrical heater has been developed recently by this research team, in order to assist in limiting the cryoinjury to the target region. The new device has been termed a 'cryoheater,' and it can work with any cryosurgical cooling technique. A prototype computerize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 15 publications
2
27
0
1
Order By: Relevance
“…In fact, due to the typical quality of ultrasound imaging, some surface areas of the organ are interpolated based on imaging data, rather than directly extracted from imaging. Given the quality of agreement between experimental data and numerical simulations presented in the current study, the typical quality of organ reconstruction for cryosurgery applications, and the fact that the defect area concept is the key for computerized planning in parallel studies, it is concluded that the numerical technique presented by Rossi et al (2007) is adequate for the purpose of computerized planning of prostate cryosurgery using the prototype algorithms presented by Lung et al (2004), Rabin et al (2004), and Tanaka et al (2006). An image of a cryoprobe, including two enlarged illustrations displaying the cryoprobe design and functionality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, due to the typical quality of ultrasound imaging, some surface areas of the organ are interpolated based on imaging data, rather than directly extracted from imaging. Given the quality of agreement between experimental data and numerical simulations presented in the current study, the typical quality of organ reconstruction for cryosurgery applications, and the fact that the defect area concept is the key for computerized planning in parallel studies, it is concluded that the numerical technique presented by Rossi et al (2007) is adequate for the purpose of computerized planning of prostate cryosurgery using the prototype algorithms presented by Lung et al (2004), Rabin et al (2004), and Tanaka et al (2006). An image of a cryoprobe, including two enlarged illustrations displaying the cryoprobe design and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…It follows that uncertainty in estimating the freezing front location in the current study, based on heat transfer simulations, is smaller than the uncertainty in estimating the freezing front location based on ultrasound imaging, in a clinical setup. Furthermore, given the quality of agreement between experimental data and numerical simulations presented in the current study, the typical quality of organ reconstruction for cryosurgery applications, and the fact that the defect area concept is the key for computerized planning in parallel studies , Tanaka et al 2006, it is concluded that the numerical technique presented by Rossi et al (2007) is adequate for the purpose of computerized planning of cryosurgery using the prototype algorithms presented by Lung et al (2004), Rabin et al (2004), andTanaka et al (2006).…”
Section: Defect Values Listed Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Towards this goal, the "force-field" algorithm has been developed [5][6], based on a series of heat transfer simulations and an analogy between the resulting temperature field and forces, which may result in cryoprobes displacement between every two consecutive simulations. A "bubble-packing" algorithm was further developed to identify the most efficient initial condition for the force-field method [7].…”
Section: Automationmentioning
confidence: 99%
“…the objective to provide results useful for understanding and designing the multi-cryoprobe procedure is commendable, critical evaluation of the Magalov et al [3] report must incorporate recent and relevant literature [4][5][6][7][8][9][10][11][12] not cited by these authors. (A few of the publications cited here were published only after [3] in archival journal, but are nonetheless relevant to the current discussion; those subjects have been widely presented in conferences in the past few years.)…”
mentioning
confidence: 99%